Investment management: an analysis of the risk-return profiles of the South African and Kenyan stock markets - Ndungu, Stanley Ngaruiya (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
This study analyses the risk-return profiles of securities and constructed portfolio of the South African and Kenya's stock markets. The analysis is done with cognisance of the dynamism that characterizes contemporary financial markets especially in the face of globalisation. To this end the study inter alia, considers the impact of the technological, information and telecommunications revolution particularly with regard to trading, delivery and settlement period. It also considers the factors that influence the business environment in each of the two markets and how these affect their risk return profiles. Key among the findings of the study are that, only a few sectors and securities in both the South African and Kenyan markets (S % and less than 1 % respectively) exhibited very high risk-return profiles while most of the rest (32 % and 40 % respectively) recorded low risk-return profiles. Overall, the business environment in South Africa is evidently better when compared to that of Kenya. Consequently, each country's business environment may be used to explain the high/low risk return profiles.
Keywords: Investments; Risk-return relationships; Johannesburg Stock Exchange; Nairobi Stock Exchange